2021
DOI: 10.1111/jdi.13533
|View full text |Cite
|
Sign up to set email alerts
|

Simplification of complex insulin regimens using canagliflozin or liraglutide in patients with well‐controlled type 2 diabetes: A 24‐week randomized controlled trial

Abstract: Aims/Introduction We investigated the potential use of canagliflozin, in comparison with liraglutide, as an alternative to bolus insulin in patients with well‐controlled type 2 diabetes mellitus receiving multiple daily insulin injection therapy. Materials and Methods In 40 patients, with glycated hemoglobin (HbA1c) levels <7.5% controlled by multiple daily insulin injection therapy, all bolus insulin was randomly switched to canagliflozin (100 mg/day) or liraglutide (0.3–0.9 mg/day) for 24 weeks. Basal insuli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
7
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 46 publications
1
7
0
1
Order By: Relevance
“…The number of Japanese participants was limited, and the findings in this population may not represent the entire diabetes population. Although the number of participants was limited, similarly low numbers of SH among Japanese PWD are reported in other studies [3,[15][16][17]. As the majority of study participants had T1DM, caution should be employed when generalizing these findings to people with T2DM.…”
Section: Discussionmentioning
confidence: 86%
See 2 more Smart Citations
“…The number of Japanese participants was limited, and the findings in this population may not represent the entire diabetes population. Although the number of participants was limited, similarly low numbers of SH among Japanese PWD are reported in other studies [3,[15][16][17]. As the majority of study participants had T1DM, caution should be employed when generalizing these findings to people with T2DM.…”
Section: Discussionmentioning
confidence: 86%
“…Abiru et al [17] reported SH events among 528 participants aged at least 26 years from the Study of Adults' Glycemia in T1DM; in this T1DM population, only 5.5% reported experiencing one or more SH events within the previous 6 months. As reported in the literature [3,[15][16][17], Japan has low rates of SH in people with T2DM and T1DM. Furthermore, in the current study, there were limited numbers of people who met the inclusion criteria for enrollment.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…In addition, basal insulin therapy has been shown to cause less body weight gain than other insulin regimens[ 9 , 10 ]. The most practical protocol for a patient is a simple one of once daily injections, with easy dose adjustment, which is associated with a good QOL and appropriate fasting glucose concentrations[ 11 , 12 ]. However, although basal insulin is useful for managing fasting blood glucose concentrations, basal insulin does not always prevent postprandial hyperglycemia[ 13 ].…”
Section: Effects Of Two Injectable Agents: Basal Insulin and Glp-1rasmentioning
confidence: 99%
“…GLP‐1RAs are an attractive alternative treatment for bolus insulin injections because of their lower risk of hypoglycemia and weight loss benefit, especially for obese patients with type 2 diabetes. A recent report showed that simplification from an intensive insulin injection regimen (basal + bolus insulin injection) to liraglutide maintained the HbA1c level with stable glucose variability in patients with well‐controlled type 2 diabetes receiving multiple daily insulin injection therapy 15 . Furthermore, the replacement of the therapy decreased the total insulin dose and quality of life score, which are significantly associated with injection frequency.…”
mentioning
confidence: 99%